Modelo de previsão para o módulo de deformação estático de concretos de cimento Portland produzidos na cidade de Santa Maria - RS - Berton, Kauana Moraes (2024)
The concrete deformation modulus is a crucial mechanical property used in structural design and serviceability limit state checks for structures. Although NBR 6118 (ABNT, 2023) currently standardizes equations to predict the concrete deformation modulus, focusing on coarse aggregate type and compressive strength, previous research indicates the influence of other factors, such as coarse aggregate properties, relative paste volume, among others. This study aims to deepen the understanding of the behavior of the concrete deformation modulus by proposing a set of specific correlation equations for Portland cement concretes produced with materials available in the city of Santa Maria – RS. To achieve this, eight concrete mix families produced by a local concrete producer were analyzed. Each family consisted of a low, intermediate, and high mix in terms of the cement-to-dry-materials ratio (m), intended for conventional, wall, and floor uses, totaling 24 formulations, with or without fly ash. All concretes were produced using the same type of cement and the same nature of fine and coarse aggregates. The experimental procedure, conducted in partnership with the local concrete producer, included mechanical tests followed by statistical analysis of the results. The study aimed to determine the most influential properties on compressive strength and deformation modulus. The most influential factors on compressive strength were the water-to-binder ratio (w/b) and the dry materials content. Regarding the behavior of the deformation modulus, significant factors were compressive strength, dry materials content, relative paste volume (RPV), and relative aggregate volume (RAV). Comparison with the normative equation (NBR 6118, 2023) revealed an overestimation of the deformation modulus results for the studied mixtures. To make the developed model applicable for predicting the behavior of local concretes, the prediction equations were simplified, considering only the concrete compressive strength as a variable. Therefore, the models were segmented into three equations suitable for conventional, wall, and floor mixes, taking into account the peculiarities of each mix. The validation of the proposed equations was performed using statistical parameters, confirming their applicability.